The complete book of home, site, and office security : - Phillips, Bill (McGraw-Hill, 2006)
This is a one-stop resource for securing and protecting homes, businesses, and valuable property. Written without technical jargon, this guide focuses on choosing, installing, and troubleshooting security devices and systems and offers insider advice on starting and running a security consulting business.